The worldview of human character in the novels Kapal Terbang Sembilan and Djampea by M. Yanis - Sulissusiawan, Ahadi; Asfar, Dedy Ari; Duantika, Prima; Wartiningsih, Agus; Shin, Chong (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
The study aims to explain M. Yanis' worldview in the novels Kapal Terbang Sembilan (1983) and Djampea (1998), written based on his experiences interacting with the Japanese and Dutch colonialists in West Kalimantan. This study used a descriptive method. The data source in this study is the novels Kapal Terbang Sembilan and Djampea by M. Yanis. This data collection was carried out using documentary techniques. Data in the form of quotations in the novel were then studied using Lucien Goldmann's genetic structuralism theory. The results of the study are as follows. First, M. Yanis' worldview in the novels Kapal Terbang Sembilan and Djampea concerns good human character. Second, the worldview contains universal values about the importance of having good character. These good characters include obedience to religious teachings, being helpful, respecting others, obeying social manners and ethics, having a pioneering soul, being friendly and polite, being devoted, and prioritising inter-ethnic friendship. M. Yanis' thoughts describe a worldview about inter-community relations with moral messages based on good character.